Performance comparison of PHP-ASP web applications via database queries - DURU, ADİL DENİZ (Association for Computing Machinery, 2015)
In the concept of the study, an empirical comparison of PHP and ASP technologies are performed. The comparison is based on the execution speed of three simple scripts. In the first phase, ASP and PHP are compared using a script that contains a for loop. Several iterations are performed starting from ten thousand to ten million and execution times are measured. Each experiment has been used for 10 times and average values of execution speed are computed. In the second phase, execution speed of PHP-MySQL and ASP-MSSQL combinations are compared. An "insert" and a "select" query using a single database table are used in a for loop. Minimum Iteration number is selected as 100 while the maximum was set to 100000 for "insert" and one million for "select" queries. It was observed that PHP-MySQL combination may have a better performance than ASP.net-MSSQL Server, in the case of both SQL queries. © 2015 ACM.
Keywords: ASP; Performance; PHP; Web application